Associations of serum pepsinogen and Gastrin-17 with Helicobacter pylori infection, sex, and age, in an asymptomatic coastal population: A cross-sectional study in Rizhao, China - Tianyi Zhang; Xiangxiang Meng; Xiaomei Wang; Shanwen Mi; Yanjie Qu; Jianxin Li; Sujun Hou; Yaocai Wang; Mengmeng Yin (PLoS ONE, 2025)
Background Pepsinogen (PG) and gastrin-17 (G-17) are widely used in the screening of gastric diseases. Our cross-sectional clinical study investigates the relationship between Helicobacter pylori (HP) infection, sex, and age on serum levels of PG and G-17 in asymptomatic subjects in Rizhao, China. Methods A total of 12,746 asymptomatic subjects were enrolled in the study between August 2023 and January 2024. Serum levels of pepsinogen I (PGI), pepsinogen II (PGII), and G-17 were measured using the chemiluminescent microparticle immunoassay method, and the PGI/PGII ratio (PGR) was calculated. HP infection was detected using the Colloidal Gold Method, and the relationship between age, sex, HP infection, and serum PG and G-17 levels was analyzed. Results HP prevalence was 19.33% in this study. The serum PGI, PGII, and G-17 levels were significantly higher in the HP-positive group compared to the HP-negative group (P < 0.001), whereas the PGR was notably lower in the HP-positive group (P < 0.001). Spearman correlation tests analysis indicated a positive correlation between HP infection and PGI, PGII, and G-17 (r = 0.144, P < 0.001; r = 0.418, P < 0.001; r = 0.268, P < 0.001), and a negative correlation with PGR (r = −0.438, P < 0.001). ROC curve shows that the AUC of the combination of PGI, PGII, PGR, and G-17 in diagnosing HP positive were 0.605 (95% CI: 0.592–0.618), 0.805 (95% CI: 0.795–0.816), 0.820 (95% CI: 0.811–0.830), and 0.709 (95% CI: 0.698–0.720), respectively. The detection rates of abnormal PG and G-17 levels were significantly higher in the HP-positive group than in the HP-negative group (P < 0.01). Males exhibited significantly higher levels of both PGI and PGII than females (P < 0.001). The G-17 levels were higher in males than females in the 50–59 age group (P < 0.05). Spearman correlation analysis revealed that serum levels of both PGI and PGII exhibited an increase with age. Serum PGI, PGII, and G-17 levels were positively correlated with age, although the relationship was weak (r = 0.228, P < 0.001; r = 0.246, P < 0.001; r = 0.042, P < 0.001). Following adjustment for sex and Helicobacter pylori infection covariates using a restricted cubic spline (RCS), the analysis revealed a significant overall association between PGI, PGII, PGR, and G-17 serum levels and age (P for overall < 0.001, P for overall < 0.001, P for overall = 0.003, and P for overall < 0.001, respectively). Furthermore, a nonlinear relationship was found between PGI, PGR, and G-17 levels and age (nonlinear P = 0.004, nonlinear P = 0.001, and nonlinear P = 0.008, respectively), whereas PGII exhibited a linear correlation (nonlinear P = 0.841). Conclusion Serum levels of PG and G-17 are associated with HP infection, sex, and age. These findings provide region-specific insights into the relationships between these biomarkers and HP infection, highlighting the importance of considering HP infection status, sex, and age in future research.